The Effectiveness Of Interactive Storytelling Method In Enhancing Language Skills Of Early Childhood Children With Language Delays - Samsu Nurfalah; Halwa Ratu Amani; Sri Widaningsih; Ira Faoza (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2026)
Background: Language delay affects 12–14% of early childhood children, significantly hindering their academic readiness and social interactions within the learning environment. Objective: This study aims to evaluate the effectiveness of the interactive storytelling method in improving receptive and expressive language skills among young children experiencing language delays. Method: Utilizing a quantitative one-group pretest-posttest design, this research involved 20 children aged 5–6 years at RA Azami selected through purposive sampling. Data were collected via structured observations and oral performance tests based on established developmental indicators, and analyzed using paired t-tests and Wilcoxon signed-rank tests alongside Cohen’s dz effect size analysis. Results: The findings revealed a significant increase in language proficiency, with the group's mean score rising from 10.15 in the pre-test to 13.95 in the post-test, representing a 37.44% performance escalation supported by a very large effect size of 4.95. Novelty: This research provides an original physical-contextual classroom intervention tailored explicitly for a homogeneous language-delayed cohort, offering a direct dialogic alternative that bypasses the infrastructure demands and screen-time risks associated with digital storytelling. Conclusion: The interactive storytelling method is an exceptionally effective, non-clinical pedagogical strategy for mitigating early language barriers, offering vital practical and operational frameworks for inclusive early childhood educators.